ANALISIS HUKUM TERHADAP KEWAJIBAN PPh ORANG PRIBADI NOTARIS DAN NOTARIS / PPAT - FRIYAN SATRIA (PREMISE LAW JURNAL, 2018)
DOSEN PEMBIMBING:1. Budiman Ginting2. Bastari3. Jelly Leviza Every taxpayer in Indonesia who has had NPWP is required to carry out his right and obligation according to the prevailing regulations. An appointed Notary/PPAT has already had NPWP. Article 28 of UU KUP, Article 14 of UU PPh, and PER-17/PJ/2015 which regulates the calculation of PPh OP Notary/PPAT for gross circulation below Rp. 4.8 million can choose to organize bookkeeping or calculating norm, while a Notary/PPAT who has his earnings Rp.4.8 million or more has to organize bookkeeping. Regulation on the calculation of PPh of individuals for a Notary/PPAT who obtains earnings from professional service and business does not meet the principle of justice, either vertically or horizontally, because ideally the same earnings will have the same amount of tax, and the bigger the earnings, the more taxable which has to be paid.Keywords: Notary, PPAT, PPh, Bookkeeping, Recording, NPWP, Taxpayer